2021
DOI: 10.3389/fped.2021.648828
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram for Predicting Bronchopulmonary Dysplasia in Very-Low-Birth-Weight Infants

Abstract: Background: Bronchopulmonary dysplasia is a common pulmonary disease in newborns and is one of the main causes of death. The aim of this study was to build a new simple-to-use nomogram to screen high-risk populations.Methods: In this single-center retrospective study performed from January 2017 to December 2020, we reviewed data on very-low-birth-weight infants whose gestational ages were below 32 weeks. LASSO regression was used to select variables for the risk model. Then, we used multivariable logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
(46 reference statements)
1
10
0
2
Order By: Relevance
“…Alicia et al found that serum NT-proBNP levels during 48–72 h of life were associated with NEC ( 20 ). Our previous studies have also found that in Chinese infants, serum NT-proBNP in the first week may be an important predictor of severe ROP and BPD ( 30 , 31 ). Prolonged mechanical ventilation and repeated intubation/extubation are important risk factors for BPD, and we also found serum NT-proBNP level could precisely predicted weaning failure of infants with RDS (ROC-AUC: 0.977; 95% CI: 0.918–0.997; p < 0.001) ( 18 ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Alicia et al found that serum NT-proBNP levels during 48–72 h of life were associated with NEC ( 20 ). Our previous studies have also found that in Chinese infants, serum NT-proBNP in the first week may be an important predictor of severe ROP and BPD ( 30 , 31 ). Prolonged mechanical ventilation and repeated intubation/extubation are important risk factors for BPD, and we also found serum NT-proBNP level could precisely predicted weaning failure of infants with RDS (ROC-AUC: 0.977; 95% CI: 0.918–0.997; p < 0.001) ( 18 ).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it is important to find other early factors that could be potential to estimate the length of hospitalization. In our previous study, we used NT-proBNP to predict BPD and ventilator weaning ( 30 , 31 ), which may influence the length of stay in hospital of preterm infants. In this study, we further found the relationship between NT-proBNP level and length of hospital stay, and it was meaningful to further explore the early predictors of the length of hospitalization of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, many predictive models for BPD have been developed using clinical variables, such as GA, BW, sex, IUGR, MV time, and HsPDA ( 25 , 26 ). As expected, smaller GA, male sex, IUGR, MV time in the first week of life and type of respiratory support on the 7th day after birth were important predictors of moderate-to-severe BPD/death, and patients with HsPDA were more likely to develop moderate-to-severe BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Some promising relevant studies regarding extubation readiness in preterm infants have already been published [146,147]. As for BPD, most clinical models of the past were reported to be poor to moderate predictors [148]; but new, promising studies with simple-to-use validated nomograms for predicting BPD in the early stage have emerged [149,150]. The integration of new technologies into clinical practice is not something in the distant future but will very soon be part of routine neonatal care.…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%